Theoretical modeling of 2,4-dichlorophenoxyacetic acid on acid-treated peanut skin: microscopic analysis via statistical physics treatment - Salah Knani; Ismahene Ben Khemis; Ana Carolina Ferreira Piazzi Fuhr; Nizar Lefi; Safwat A. Mahmoud; Guilherme Luiz Dotto; Abdulaziz Alenazi; Ridha Selmi (Scientific Reports)
Abstract In this study, the experimental adsorption isotherms of 2,4-dichlorophenoxyacetic acid (2,4-DA) on peanut skin treated with sulfuric acid were analyzed under different temperatures and characterized by Fourier transform infrared spectroscopy. The adsorption mechanism was interpreted based on statistical physics theory using the homogeneous double-layer model with one energy (HDLM1E). The modeling results indicated that the removal of 2,4-DA molecules occurred through a multi-interactive adsorption mechanism at temperatures of 25, 35, and 45 °C (0.76 < n < 0.99). In comparison, at 55 °C, a monomolecular adsorption mechanism was observed (n = 1.00). At 25 °C, the adsorbent demonstrated excellent performance in the 2,4-DA removal, with a maximum capacity of 244.33 mg/g. The increase in temperature reduced the adsorbent’s performance in removing 2,4-DA molecules because it increased thermal collisions, which harmed the system. From an energetic point of view, the adsorbent showed less effectiveness in removing the herbicide at high temperatures, indicating an exothermic adsorption process. The surface adsorption energies ranged from 4.72 to 6.06 kJ/mol, indicating the predominance of a physisorption mechanism. Therefore, the adsorption process at low temperatures is essential for industrial applications to ensure efficient wastewater treatment. This result is possible using an adsorbent from peanut skin subjected to acid treatment. Finally, the creation of an adsorbent from acid-treated peanut (Arachis hypogaea) skin presents an excellent alternative, yielding exceptional results in removing the 2,4-DA herbicide.